Vrednotenje sistemov javnega potniškega prometa v izbranih občinah Slovenije - Ogrin, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
In Slovenia public transport is in decline already for few decades. At the same time, the country faces a strong growth of motorisation. Its growth was even stronger than in most of EU countries, which resulted that Slovenian transport system is very expensive, it causes excessive air pollution and is far from sustainable. However, in some cities and areas in last years we can notice some signs of public transport recovery. The article compares public transport systems in selected Slovenian municipalities and shows which measures were taken to implement recovery of transport systems.
Keywords: javni prevoz; mesta; mestni promet; potniški promet; Slovenia; Slovenija; sustainable development; trajnostni razvoj